Pilot study on the learning success of students in service-learning compared to other teaching and learning formats - Maren Schlegler; Susanne Koch (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2022)
The world is increasingly characterized by global and national disasters and crises. To cope with these, social cohesion is indispensable - and this in turn requires that young people are taught how to become responsible citizens. Strengthening students' personal development and social commitment are therefore key responsibilities of universities. Service-learning is one possibility to integrate these into teaching and learning, however studies on the effectiveness of service-learning in Europe - and especially in Germany - are rare. This paper examines the effects of service-learning, whereby three different study groups are compared. The study includes n=132 bachelor and master students, and shows that the groups' outcomes hardly differ from one another. It can tentatively be said that there are only minor differences between the formats and that service-learning is equal to more traditional teaching-learning formats, but again is not superior with regard to the variables investigated. – – Die Welt ist zunehmend von globalen und nationalen Katastrophen und Krisen geprägt. Um diese zu bewältigen, ist sozialer Zusammenhalt unabdingbar - der wiederum setzt voraus, dass junge Menschen zu verantwortungsvollen Bürgern erzogen werden. Die Stärkung der Persönlichkeitsentwicklung und des gesellschaftlichen Engagements der Studierenden ist daher eine zentrale Aufgabe der Hochschulen. Service-Learning ist eine Möglichkeit, diese in die Lehre und das Lernen zu integrieren. Studien über die Wirksamkeit von Service-Learning in Europa - und insbesondere in Deutschland - sind jedoch rar. Die vorliegende Arbeit untersucht die Auswirkungen von Service-Learning, wobei drei verschiedene Studiengruppen verglichen werden. Die Studie umfasst n=132 Bachelor- und Masterstudenten und zeigt, dass sich die Ergebnisse der Gruppen kaum voneinander unterscheiden. Die Ergebnisse deuten darauf hin, dass es nur geringe Unterschiede zwischen den Formaten gibt und dass Service-Learning den traditionelleren Lehr-Lern-Formaten gleichwertig, aber wiederum nicht überlegen ist, was die untersuchten Variablen betrifft.
Keywords: 330; Studierende; Lernmethode; Wirtschaftspädagogik; Projektmanagement; Ehrenamtliche Arbeit; Verantwortung; Deutschland; Europa